Integrating computational thinking skills in secondary education: A feasibility study - Wan Mohd Ghazali, Khadijah; Osman, Mashanum; Othman, Zuraini; Omar, Masitah Seikh (2024)
This feasibility study investigates the practicality of incorporating Computational Thinking (CT) education into secondary school curricula, aiming to equip students with essential 21st-century skills. The study assesses the readiness of educational institutions, teachers and students to embrace CT as an integral part of their learning journey, identifying potential challenges and barriers to successful implementation. To achieve these objectives, the research examines the existing landscape of CT education, evaluates teacher preparedness, analyses student receptiveness, and explores resource requirements and best practices from around the world. As part of this investigation, an immersive learning approach will be integrated. A five-day training program was implemented, featuring a comprehensive curriculum that covered key CT concepts, problem-solving techniques, presentation skills, and problem-based learning aligned with Sustainable Development Goals. The program included pre- and post-surveys to measure students' understanding of CT concepts and practical projects to apply their learning. Results showed consistent improvement in students' self-reported understanding of CT skills and their ability to apply these concepts to real-world problems. The study reveals that integrating CT into secondary education is not only necessary but also highly beneficial. The study emphasizes that a holistic educational reform incorporating leadership, technology and curriculum adjustments is essential for the successful implementation of CT education. The study also highlights the importance of aligning CT education with current educational policies and trends, such as KSSM (Kurikulum Standard Sekolah Menengah - Secondary School Standard Curricular), which advocate for the inclusion of CT as a fundamental practice of science education. In conclusion, this study provides valuable insights and recommendations for educational policymakers, administrators, and educators interested in enhancing CT skills in secondary students.